14. ANALYSIS OF DRUG-RELATED PROBLEMS (DRPs) IN THE USE OF ANALGESICS IN CANCER PATIENTS AT THE 108 MILITARY CENTRAL HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objective: To assess the characteristics of drug-related problems (DRPs) and their causes in pain management for cancer patients at the 108 Military Central Hospital. Methods: A prospective, cross-sectional study was conducted on 471 hospitalized cancer patients. DRPs were identified using the PCNE classification system version 9.1, through medication record review, patient interviews, and multidisciplinary collaboration.Results: The proportion of patients with DRPs was 22.1%. Among them, the most common DRP was suboptimal treatment effectiveness (74.1%), mainly due to subtherapeutic dosing (45.9%) and patient non-compliance (45.1%). Statistical analysis showed a significant reduction in moderate and severe pain after 24 hours of treatment (p < 0.001).Conclusion: DRPs in cancer pain management remain common, especially those related to inappropriate dosage selection and patient adherence
Keywords: DRPs; cancer pain; clinical pharmacist; PCNE; causes of DRPs.